AN INVESTIGATION INTO SEMANTIC AND PRAGMATIC FEATURES OF UTTERANCES DENOTING NEGATION WITHOUT CONTAINING NEGATIVE ELEMENTS IN ENGLISH AND VIETNAMESE - LÊ HUY HOÀNG (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study reports an investigation into semantic and pragmatic features of utterances denoting negation without containing negative elements in English and in Vietnamese. It attempts to find out the similarities and differences as well as some outstanding advantages of applying semantics and pragmatics in studying English as well as Vietnamese. The research data are collected from English and Vietnamese best-seller novels. After collecting the data, they are analyzed both quantitatively and qualitatively. In this study, for the sake of contrastive analysis of negative sentences in English and Vietnamese, descriptive and comparative methods are chosen to be the main method of the study. By these methods, the study intends to describe, classify and analyze English and Vietnamese utterance denoting negation based on semantic and pragmatic features. The main findings of the study are the statistics on the frequency of negative sentence types, the structure of negative sentences in English and Vietnamese, the aims of negative sentences in English and in Vietnamese and the similarities and differences between English and Vietnamese negative sentences in terms of structures and uses. These results obtained from the research help understand how to use negative sentences correctly. Finally, these results aim to provide a new look at the new approach of linguistic theory and to suggest the new way of teaching and learning negative sentences